Research of the Allowable Velocity of Chain Drive of Quantitative Conveyor - Shang Shibo; Wang Honglei; Yuan Hua (Jixie chuandong)
According to the loading speed requirements of the 50 tons skip loading by quantitative conveyor,to improve the operation reliability of the transmission chain under overload and at the velocity of 1.2m/s,the combination and optimization of sprocket tooth z,chain pitch pand allowable speed v optimization are solved.A method to predict the chain allowable speed is presented,according to the existing small-pitch chain parameters from GB/T 5269-1985,the theoretical formula and the relationship curves between p&vare determined by MATLAB data fitting model,the large pitch chain allowable speed is solved.The calculation shows that p=200 &z=12meet the requirements of the loading speed and nearly consistent with TSUBAKI’s sample.The results provide a theoretical basis for design and ordering of prototype,also can provide a reference for parameter selection of large chain.